Optimization of the Extraction of the Magnolia officinalis Polysaccharides Using Response Surface Methodology - Lan, M.B.; Guo, J.; Zhao, H.L.; Yuan, H.H. (Asian Journal of Chemistry, 2012)
Magnolia officinalis is an important Chinese traditional herb in Chinese medicinal soups that have been used for centuries to treat thrombotic stroke, gastrointestinal complaints, anxiety and nervous disturbance. The Magnolia officinalis polysaccharides are the main active ingredients in the decoction. The objective of this study is to investigate the yield of polysaccharides from Magnolia officinalis under different extraction temperatures, extraction times and water/material ratios by using the response surface methodology (RSE), with a Box-Benhken design (3 factors and 3 levels). The optimal water extraction conditions for polysaccharides are as follows: an extraction temperature of 93.7 ºC, an extraction time of 3.25 h and a water/material ratio 26.2:1. Under these conditions, the yield of polysaccharides reached a peak value of 5.29 ± 0.03 % (w/w).